2019
DOI: 10.1093/pubmed/fdz030
|View full text |Cite
|
Sign up to set email alerts
|

Daily music listening to reduce work-related stress: a randomized controlled pilot trial

Abstract: Background Literature shows that music can reduce stress conditions. This pilot study investigated the effects of music listening on work-related stress and well-being in healthcare professionals. Method A total of 45 subjects were randomly assigned to three treatment groups: No Music, Individualized Music and Melomics-Health Listening. Music groups experienced a daily 30-min-playlist listening for 3 weeks at home. The Mauger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
1
24
0
1
Order By: Relevance
“…The result of this study therefore is in line with that of Dolezal and Spitzbart-Glasl (2015) who found that acoustic quality of building components can have impact on the ecological performance of the whole building. Backed by the classical theories of music, mood and movement championed by Murrock and Higgins (2009), this study keyed into the results of other studies (Batt-Rawden & Storlien, 2019;Challe, 2015;Jiang et al, 2019;Jo & Jeon, 2020;Raglio et al, 2020;Yi & Kang, 2019) that affirmed the positive roles of music towards ensuring socioecological sustainability and promoting the well-being of building users in our buildings. The study has strengthened the result of Okoye et al (2020b) which found that among the sustainability dimensions, social sustainability performance of buildings was mostly affected, but in the antithetical direction.…”
Section: Test Of Hypothesismentioning
confidence: 68%
See 2 more Smart Citations
“…The result of this study therefore is in line with that of Dolezal and Spitzbart-Glasl (2015) who found that acoustic quality of building components can have impact on the ecological performance of the whole building. Backed by the classical theories of music, mood and movement championed by Murrock and Higgins (2009), this study keyed into the results of other studies (Batt-Rawden & Storlien, 2019;Challe, 2015;Jiang et al, 2019;Jo & Jeon, 2020;Raglio et al, 2020;Yi & Kang, 2019) that affirmed the positive roles of music towards ensuring socioecological sustainability and promoting the well-being of building users in our buildings. The study has strengthened the result of Okoye et al (2020b) which found that among the sustainability dimensions, social sustainability performance of buildings was mostly affected, but in the antithetical direction.…”
Section: Test Of Hypothesismentioning
confidence: 68%
“…Nevertheless, a trial study conducted by Raglio et al (2020) suggested that daily listening to music could reduce work-related stress at home and that the effect may be related not only to individual musical preferences and familiarity, but also to specific music structure and parameters. Fundamentally, the goal of sustainable building is to create buildings that preserve the environment and conserve natural resources, as well as to provide a 'healthy' environment for its occupants (Hodgson, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque en principio se asumió el criterio convencional de considerar como diferencias significativas entre grupos aquellos contrastes con un valor de p<.05, entendiendo que este criterio es necesariamente arbitrario, se resaltan también como relevantes valores cercanos como p<.07. La convención de usar valores de p<.05 ha sido criticada con frecuencia (p.ej., Cohen, 1994) y un valor conservador de p<.07 se sigue usando en estudios recientes como indicador de una tendencia a la significación (por ejemplo, Raglio et al, 2019).…”
Section: Análisis Estadísticounclassified
“…Music has also shown a specific role in stress reduction, in the field of pain, work, daily life, etc. [ 10 , 11 , 12 ].…”
mentioning
confidence: 99%